Evaluation of the cytological changes of oral mucosal cells in Smokers by using Exfoliative Pap Stain. (Mustansiria Dental Journal, 2018)
Oral cancer is a major public health issue worldwide; it remains a highly lethal anddisfiguring disease. in Iraq little is written regarding the occurrence of oral cancer.The aim of this study is To examine the effect of smoking oral mucosa cytological.Hundred men aged between 40 and 70, comprising 50 smokers and 50 non smokers.Material for exfoliative cytology was collected with a metal spatula from thelateral border of the patient’s tongue and from the floor of the mouth and the sampleswere then submitted for Papanicolaou staining. Then cytologic smears were classifiedaccording to Papanicolaou’s classification. the results of the current study reveals thatthere is a significant association between smoking (number of cigarette smoked perday and the duration of smoking (year) and the occurrence of cytological changes inthe oral mucosa ,p